Efficient [Cu(NHC)]‐Catalyzed Multicomponent Synthesis of Pyrroles. Issue 18 (17th August 2017) - Dang, Tuan Thanh; Seayad, Abdul Majeed
Abstract: Efficient [Cu(NHC)]‐catalyzed syntheses of pyrroles via two and three‐component coupling methods are described. Various 1, 2‐, 1, 2, 3‐, 1, 2, 3, 5‐ and fully substituted pyrroles were readily accessible through a suitable choice of ketone, primary amine and diol in a three‐component reaction. The N‐unsubstituted pyrrole formation is also feasible through a two‐component reaction involving a β‐amino alcohol and a ketone. Abstract : Pyrrole‐mania ! A [Cu(NHC)] (NHC=N‐heterocyclic carbene) catalyst efficiently converts readily available diols, ketones, β‐amino alcohols, and amines to various substituted pyrroles through a two‐ or three‐component reaction in up to 95 % isolated yield.